Use of Religious Coping among Singaporean Parents of Children with Cancer - ÇAKSEN, HÜSEYIN (Pakistan Journal of Medical & Health Sciences, 2025)
Cancer is one of the leading causes of disease-related death and treatment-associated morbidity in children with an increasing trend in recent decades worldwide1. The diagnosis of childhood cancer not only affects the life of the child but also impacts the lives of the caregivers as well. Children with cancer and their parents often experience symptoms of stress, anxiety, or depression. Many parents of children with cancer have used religious coping in many parts of the world including North and South America, Europe, Middle Eastern, Africa and Asia1-8. Religion is a law established by Allah and it leads people to peace, goodness, blessings, and salvation in this world and in the hereafter9. Religious coping is a means of seeking Allah’s help, trusting and taking refuge in Allah, finding solace in religious provisions/teachings, and praying/worshiping more than usual during stressful events of life such as illness, calamity, death, or circumstances where a person is helpless2-10. Herein, we discuss the religious coping strategies of Singaporean parents of children with cancer to draw attention to the importance of religion and religious coping. Although many studies have been reported on religious coping strategies of parents of children with cancer in the United States, Western, and Middle Eastern countries, there are limited studies on this subject in Singapore. Fourteen (25.4%) of the 59 Singaporean parents of pediatric cancer patients used some form of spirituality such as formal prayer, laying on of hands, seeking help from a bomoh, and temple medium11. Tan et al12 noted that Singaporean mothers of children with cancer turned to spirituality and well supported by spirituality. Parents believed that the diagnosis of cancer was part of a Divine plan. Spirituality through prayer was an active emotion-focused coping strategy, and belief in Divinity gave parents a sense of hope. Religious practices also helped parents to process complicated emotions and decrease the burden of caregiving12. Leow et al13 found that spiritual-related interactions scores of Singaporean caregivers of patients with cancer increased from baseline to 2 months. Caregivers with higher social support satisfaction and who had a religion predicted higher quality of life. Non-Chinese caregivers, caregivers who had been in the home hospice for a longer duration, and caregivers and patients who had a religion had higher spiritual perspective scale scores13. The majority of the South Asian parents of children with cancer, regardless of their religious affiliation, mentioned about the significance of prayer and other religious practices in helping them cope with their child’s diagnosis, treatment, and recovery. They emphasized their faith in Allah and often read verses from holy texts (e.g., the Quran and Gita) relating specifically to asking for recovery from disease and pain, which in itself was viewed as part of managing the health situation14. In conclusion, we would like to emphasize that religious coping is frequently used by Singaporean parents of children with cancer due to its psychospiritual and mental benefits. Second, we believe that health professionals should recognize and respect parents' religious and spiritual needs and encourage parents to use religious coping strategies. Lastly, we recommend that multicenter and comprehensive studies on religious coping of parents of children with cancer should be conducted in societies with different sociocultural characteristics. These studies will guide health professionals and will be useful for parents of children with cancer in clinical practice. Author Contributions Conceptualization, HÇ; Writing–original draft, HÇ; Writing–review & editing, HÇ. Declaration of Conflicting Interests The author declared no potential conflicts of interest with respect to the research, authorship, and/or publication of this article. Funding The author received no financial support for the research, authorship, and/or publication of this article. Ethical Approval This study was a review of published literature and no ethical approval required.